Impact of cumulative SBP and serious adverse events on efficacy of intensive blood pressure treatment: a randomized clinical trial - Rueda-Ochoa, O; Rojas, L; Ahmad, S; Van Duijn, C; Ikram, M; Deckers, J; Franco, O; Rizopoulos, D; Kavousi, M (Lippincott, Williams and Wilkins, 2019)
BACKGROUND: Intensive blood pressure lowering is increasingly gaining attention. In addition to higher baseline blood pressure, cumulative SBP, visit-to-visit variability, and treatment-induced serious adverse events (SAEs) could impact treatment efficacy over time. Our aim was to assess the impact of cumulative SBP and SAEs on intensive hypertension treatment efficacy in the Systolic Blood Pressure Intervention Trial (SPRINT) population during follow-up. METHODS: Secondary analysis of the SPRINT study: a randomized, controlled, open-label trial including 102 clinical sites in the United States. We included 9068 SPRINT participants with 128 139 repeated SBP measurements. Participants were randomly assigned to intensive (target SBP < 120 mmHg) versus standard treatment (target SBP between 135 and 139 mmHg). We used cumulative joint models for longitudinal and survival data analysis. Primary outcome was a composite outcome of myocardial infarction, other acute coronary syndromes, acute decompensated heart failure, stroke, and cardiovascular mortality. RESULTS: Although intensive treatment decreased the risk for the primary SPRINT outcome at the start of follow-up, its effect lost significance after 3.4 years of follow-up in the total SPRINT population and after 1.3, 1.3, 1.1, 1.8, 2.1, 1.8, and 3.4 years among participants with prevalent chronic kidney disease, prevalent cardiovascular disease, women, black individuals, participants less than 75 years, those with baseline SBP more than 132 mmHg, and individuals who suffered SAEs during follow-up, respectively. CONCLUSION: The initial beneficial impact of intensive hypertension treatment might be offset by cumulative SBP and development of SAEs during follow-up.